PEMBUATAN GAME KOMPUTER KOMDIG’S JOURNEY SEBAGAI SUPLEMEN PELAJARAN SIMULASI DAN KOMUNIKASI DIGITAL - Lies Yulianto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Many students of SMK Negeri 3 Pacitan play games while in the computer laboratory. Students choose to play games than learn with the teacher. The notes in the Counseling Guidance section also found many cases of students not go to school only to play online games. They skip to school just to play online games that are more fun than studying in boring school. The design of this research is Research & Development and tries to accommodate the students' interest in playing games by making computer games that contain lessons. Computer games that are made are used as learning media in the classroom so that students diligently study with different methods, students are not saturated just listening to the teacher explain the material. The game that was created was named Si Komdig’s Journey with type Role Playing Game in the form of theadventure of the Komdig in seeking knowledge. On that adventure, theknowledge and education is inserted. And the results of a trial of 30 students packed with Classroom Action Research knowned that the use of the Si Komdig’s Journey game can improve student achievement and student independence in learning. Keywords: computer game, learning game, Si Komdig’s Journey, game for learning